2005
DOI: 10.1309/v8xmk5r78q96v090
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Malignant Peripheral Nerve Sheath Tumor

Abstract: We reviewed the clinicopathologic features of 5 cases of malignant peripheral nerve sheath tumor (MPNST) manifesting in superficial locations associated with cutaneous neurofibromas (4 cases) or superficial peripheral nerve (1 case). Four cases had spindle cell morphologic features and were at least focally positive for S-100 protein, whereas the associated benign neural elements had more extensive S-100 immunoreactivity. The single epithelioid case was diffusely and strongly positive for S-100 protein. Melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 26 publications
0
72
1
Order By: Relevance
“…It seems that the current treatment of these highly malignant tumors, however, is not that pessimistic. As some authors have pointed out, the survival rates of patients with MPNSTs were significantly better for superficial tumors, such as MPNST of the scalp [5]. Other authors, however, believe that the present data does not allow final conclusions about the prognosis of MPNST of the scalp, because these results are based on a small patient population with primarily short follow-up periods [17].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It seems that the current treatment of these highly malignant tumors, however, is not that pessimistic. As some authors have pointed out, the survival rates of patients with MPNSTs were significantly better for superficial tumors, such as MPNST of the scalp [5]. Other authors, however, believe that the present data does not allow final conclusions about the prognosis of MPNST of the scalp, because these results are based on a small patient population with primarily short follow-up periods [17].…”
Section: Discussionmentioning
confidence: 68%
“…A variety of terminologies, including neurofibrosarcoma, neurogenic sarcoma, malignant schwannoma, and malignant neurilemomma have been used to describe the tumor. As defined by the World Health Organization, however, the universal or standard terminology should be malignant peripheral nerve sheath tumor [1-5]. Although the incidence of malignant peripheral nerve sheath tumor of the scalp is very low, it is highly malignant and is associated with poor prognosis [1-3].…”
Section: Introductionmentioning
confidence: 99%
“…Most involve major nerves, 54 although rare tumors may occur in unusual locations such as the skin. 55 For unclear reasons, EMPNST accounts for the great majority of MPNST that arises within schwannomas (an exceedingly rare event). 51,56 EMPNSTs are aggressive lesions, with distant metastases eventually occurring in B50% of patients, typically to the lungs.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…As some authors have indicated, the survival rates of patients with MPNSTs were significantly better for superficial tumors (11). Positive tumor margins are defined as the most important prognostic marker (12).…”
Section: Figure 1 the Tumor Cells Are Pleomorphic Obviously With Ovamentioning
confidence: 99%